Detection of lycopene in local watermelon (Citrullus Lanatus (thunb.) Matsum. And NakaI) by using high performance liquid chromatography (HPLC) / Noratiqah Padali - Padali, Noratiqah (2015)
Malaysia has many types of local fruits that contain high antioxidant activity that distributed as seasonal fruits or non-seasonal fruits. Watermelon is one of non seasonal fruits in Malaysia. Major carotenoid present in red-fleshed watermelon is lycopene. There are limited studies on detection and quantification of phytocemical and antioxidant activities in local watermelon Citrullus lanatus [Thunb] Matsum and Nakai compared with many fruits and vegetables but the aim of in this study are to identify of lycopene in local watermelon by using high performance liquid chromatography (HPLC) with diode-array detector (DAD) and to choose the best method for mobile phase that provide good separation for detection of lycopene by using high performance liquid chromatography (HPLC). HPLC was chosen as an analytical instrument to identify lycopene in local watermelon. Hexane extraction from watermelon juice was used for sample preparation before the sample was run on HPLC analysis. There were two methods of mobile phase was used to detect lycopene in this method. The methods for choosing mobile phase of HPLC were isocratic and gradient methods. Acetonitrile was chosen in isocratic method following from confirmation of TLC. Meanwhile acetonitrile and ionized water were chosen as mobile phase in gradient method. Result of identification of lycopene was compared between two methods of mobile phase, which show the highest peak for both lycopene standard and sample. In conclusion, gradient method was considered as best method for identification of lycopene in local watermelon Citrullus lanatus [Thunb] Matsum and Nakai which used binary mobile phase of acetonitrile and ionized water that peak show retention time 15.53 minutes.